Epidemiology of colorectal cancer in Turkey: A cross-sectional disease registry study (A Turkish Oncology Group trial) - (:unkn) unknown (AVES, 2015)
Background/Aims: This study aimed to determine the epidemiological characteristics of colorectal cancer in Turkey. Materials and Methods: In this multicenter, prospective, and cross-sectional registry study, data for 968 patients with colorectal cancer from 21 centers in 7 geographic regions were analyzed. Results: Diagnosis was colon cancer in 662 (68.4%) and rectum cancer in 306 (31.6%) patients. In total, 60.9% of patients was male; mean age was 58.9 +/- 12.6 years. Among patients, 15.0% was drinking alcohol, 17.5% was smoking, 1.5% had familial history of polyposis, 15.0% had diabetes mellitus, 1.0% had inflammatory bowel disease. Fruit and vegetable consumption was low (<3 times/week) in 35.5% and red meat consumption was high (>= 3 times/week) in 47.4% of the patients. Median time-to diagnosis was 3.0 months and 4.0 months for patients with colon and rectum cancer, respectively. Mean body mass index was >25 in all group of patients. Distal rectum (61.3%) and sigmoid colon (36.8%) were the most common locations of cancer, for rectum and colon respectively. In total, 85.6% of patients were operated; 25.8% had emergency surgery. Low anterior resection rate was 64.2% in rectum cancer. In majority (89.8%) of the patients with rectum cancer who received preoperative treatment, conventional chemo-radiotherapy regimen was given. pTNM staging at diagnosis showed that stage III and IV patients were in majority (35.9% and 29.7%, respectively). Conclusion: Colon cancer is more frequent than rectum cancer in Turkey. Colorectal cancer patients are diagnosed at later stages. Most of the cases were operated. Interregional differences for risk factors are worthwhile for evaluation in future trials.
Keywords: Colorectal cancer; epidemiology; risk factors; Turkey; RISK-FACTORS; SURVEILLANCE